Kepastian Hukum Indonesia Carbon Exchange dalam Praktik Pedagangan Karbon pada Manifestasi Green Economy di Indonesia - Malik, Muhammad Maulana; Barkatullah, Abdul Halim (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This Research Aims To Assess The Extent To Which Regulations Related To Carbon Trading Practices In The Indonesia Carbon Exchange Have Impacts And Benefits On The Manifestation Of A Green Economy In Indonesia. Using Normative Legal Methods Which Is Descriptive And Utilize Statutory And Conceptual Approaches, Researchers Look For And Collect Laws And Regulations Relating To Carbon Trading In The Manifestation Of A Green Economy And Afterwards Strengthen Theory From Books Or Legal Literature Followed By Data Collection Tools In The Form Of Documents. The Binding Force Of The Kyoto Protocol And The Paris Agreement Makes Made Indonesia Consider It Necessary To Immediately Follow Up The Program On The Nationally Determined Contribution By Presenting A Carbon Trading Scheme. Through Pojk Number 14 Of 2023, Idxcarbon With Its Three Pillars Of Implementation (Measured, Reasonable And Efficient) Provides A Basic Explanation Of The Rules Related To The Implementation Of Carbon Trading Practices And Also Provides Accessibility To Trading Parties Through Their Rights And Obligations. The Significance Of Carbon Trading Practices Towards The Realization Of A Green Economy In Several Countries With Low Carbon Footprint Status Is An Important Barometer For Other Countries, Especially Indonesia. As An Inseparable Part Of The Green Economy, The Actualization Of Carbon Trading Practices Through Idxcarbon Will Have An Effect On Sustainable Development. The Same Thing Will Also Have A Positive Impact On The Effectiveness Of The Energy Sector By Implementing Ndc And Realizing Net Zero Emissions And Starting To Shift To New Renewable Energy Which Will Provide Benefits To Realize The Mandate Of The 1945 Constitution Of The Republic Of Indonesia Regarding Providing A Decent Life For All Citizens.